Salmonella pathogenicity island-14 is a critical virulence factor responsible for systemic infection in chickens caused by Salmonella gallinarum - Hu, Zuo; Ojima, Shinjiro; Zhu, Zhihao; Yu, Xiaoying; Sugiyama, Makoto; Haneda, Takeshi; Okamura, Masashi; Ono, Hisaya K.; Hu, Dong-Liang (Frontiers in Veterinary Science, 2024)
Salmonella enterica serovar Gallinarum (S. gallinarum) is an important host-specific pathogen that causes fowl typhoid, a severe systemic, septicemic, and fatal infection, in chickens. S. gallinarum causes high morbidity and mortality in chickens and poses a significant burden and economic losses to the poultry industry in many developing countries. However, the virulence factors and mechanisms of S. gallinarum-induced systemic infection in chickens remain poorly understood. In this study, we constructed a Salmonella pathogenicity island-14 (SPI-14) mutant strain (mSPI-14) of S. gallinarum and evaluated the pathogenicity of mSPI-14 in the chicken systemic infection model. The mSPI-14 exhibited the same level of bacterial growth and morphological characteristics but significantly reduced resistance to bile acids compared with the wild-type (WT) strain in vitro. The virulence of mSPI-14 was significantly attenuated in the chicken oral infection model in vivo. Chickens infected with WT showed typical clinical symptoms of fowl typhoid, with all birds succumbing to the infection within 6 to 9 days post-inoculation, and substantial increases in bacterial counts and significant pathological changes in the liver and spleen were observed. In contrast, all mSPI-14-infected chickens survived, the bacterial counts in the organs were significantly lower, and no significant pathological changes were observed in the liver and spleen. The expression of interleukin (IL)-1β, IL-12, CXCLi1, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ in the liver of mSPI-14-infected chickens were significantly lower than those in the WT-infected chickens. These results indicate that SPI-14 is a crucial virulence factor in systemic infection of chickens, and avirulent mSPI-14 could be used to develop a new attenuated live vaccine to prevent S. gallinarum infection in chickens.